Institusi Pengelola Zakat Dalam Hukum Positif Di Indonesia - Abdullah, Junaidi (ZISWAF, 2018)
Zakat is a property that must be set aside by a Muslim or an entity that is owned by Muslims in accordance with the provisions of religion to be given to those who are entitled to receive it. Zakat should be managed properly and professionally, so that the benefits of zakat can prosper the people and can alleviate poverty and can turn mustahik into muzakki. In Indonesia, the government has made several regulations on zakat, namely with the enactment of Law number 38 of 1999 concerning the management of Zakat and has been revised by Law No. 23 of 2011. In the Law that carries out zakat management are institutions officially recognized by the government. These institutions are BAZNAS and LAZ. The form of zakat management carried out by BAZNAS and LAZ starts from the collection, distribution, utilization and reporting.